The Influence of GRA and TOPSIS for Assortment of Green Supply Chain Management Strategies in Cement Industry - P Muralidhar; K Ravindranath; V Srihari (International Journal of Supply Chain Management, 2013)
The present paper aimed at proposing new strategies for evaluating the green supply chain management for enhancing the priority to environmental factors in cement manufacturing life cycle analysis, there by reducing the carbon foot prints. These strategies help in producing eco-friendly products there striking the balance between economy and environment. Initially green supply chain priorities are defined by using grey relational analysis (GRA). The priority weights obtained by GRA method is used to determine the weight for each indicator selected in the present study and then GRA is combined with TOPSIS methodology to obtain the priority for level-II measurement indicators used in the present study. These strategies will influence the decision making priorities during cement manufacturing. Keywords - Green Supply Chain Management (GSCM), strategy prioritization, Grey Relational Analysis (GRA), TOPSIS, Life Cycle Analysis (LCA)